Ethical considerations in the regulation and use of herbal medicines in the European Union - Gatt, Anthony Raphael; Vella Bonanno, Patricia; Zammit, Raymond (Frontiers in Medical Technology, 2024)
The regulation and use of herbal medicines is a topic of debate due to concerns about their quality, safety, and efficacy. EU Directive 2004/24/EC on Herbal Medicinal Products was a significant step towards establishing a regulatory framework for herbal medicinal products in the EU, and bridging the gap between conventional and herbal medicines. This Directive allows herbal medicinal products to be marketed in the EU through full marketing authorisation, well-established use, and traditional use of herbal medicinal products. The framework relies on the correlation between the therapeutic claims of herbal medicine and the scientific evidence backing them up: the greater the claims made regarding medicinal benefits, the more evidence is required to substantiate its efficacy and safety. This regulatory framework acknowledges and incorporates traditional knowledge when evaluating herbal medicines, showcasing a balanced approach that values cultural traditions while mandating monographs for traditional herbal medicinal products. Excluding herbal medicines completely limits access to affordable treatment, particularly when they serve as the only alternative for some, and protects consumer autonomy. This EU framework could therefore serve as a practical guidance for the use and regulation of herbal medicines, even outside the EU. In conclusion, it is argued that the same moral imagination and courage shown by regulators in the case of herbal medicines could perhaps be used in the regulatory frameworks of other healthcare products.